KOHESIVITAS DAN SOCIAL LOAFING DALAM PEMBELAJARAN KELOMPOK PADA SISWA SMAN 1 INDRALAYA - Rita, Rita; Mardhiyah, Sayang Ajeng; Fikri, Muhammad Zainal (Universitas Muhammadiyah Jember, 2019)
The research aims to determine the relationship between cohesiveness and social loafing on group learning at SMAN 1 Indralaya. The hypothesis of this research as a relationship between cohesiveness and social loafing on group learning at SMAN 1 Indralaya. The subject on this research was student of SMAN 1 Indralaya. The collecting technique using nonprobability sampling with a purposive sampling. The population on this research was 772 students and the sample was 250 students based on Isaac and Micheal theory. Cohesiveness and social loafing was measured by the scale of Cohesiveness and Social Loafing, with reference to the component of cohesiveness from Forsyth (2010) and dimensions of social loafing from Chidambaram and Tung (2005).The result of this research indicate cohesiveness has a relationship with social loafing on students of SMAN 1 Indralaya with a correlation coeffisien - 0.745 and p = 0.000 (p<0.05). Thus the hypothesis is accepted.